Adapting Mobility-as-a-Service for Developing Cities : A Context-Sensitive Approach - Bianchi Alves, Bianca; Wang, Winnie; Moody, Joanna; Waksberg Guerrini, Ana; Peralta Quiros, Tatiana; Velez, Jean Paul; Ochoa Sepulveda, Maria Catalina; Alonso Gonzalez, Maria Jesus (World Bank, Washington, DC, 2022)
People living in cities have more mobility options than ever before. Making the most out of expanding travel choices for cities and their residents will require integration among different mobility services. Mobility-as-a-Service (MaaS) can provide an organizing framework for integrating multiple mobility options and shaping how they can work together to provide a more seamless travel experience and support broader development outcomes in developing cities. This report contextualizes the concept of Mobility-as-a-Service (MaaS) for cities in low- and middle-income countries, discussing how this powerful framework may advance sustainable mobility and development goals. To reap the greatest benefits, MaaS implementation requires government leadership, systematic thinking around societal goals, and new technical capabilities—all important capacities that may not be readily available in developing cities. To begin building these capacities, this publication discusses the critical issues involved in deploying MaaS from the perspectives of supply, demand, technology, business, and governance.